Estimation of exposure of medical staff employed in Radionuclide Division of Endocrinology Department and Radioactive Wastes Disposal Facility in Holycross Cancer Centre in Kielce - Kowalska, Aldona; Żórawska, Anna; Chruściak, Dariusz; Niziołek, Jacek; Jurkiewicz, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
The article presents two main problems related to radiological protection in Radionuclide Division of Endocrinology Department of Holycross Cancer Centre in Kielce. The first one refers to the Division structure and designed functional system of rooms, the traffic of the medical staff and patients as well as solid and movable shields applied in the Division, and the procedures of the contamination measurement. Then we introduced the structure and the organisation of the work in Radioactive Wastes Disposal Facility that is a integral part of Radionuclide Division. The second one is the control of employed medical staff exposure. We presented results on doses received from outside sources by the employed medical staff. They were measured using the individual film dosimeters, digital dosimeters - Stephen 6000 and dosimeter FH-40G. Then, using the multi-chanel analyser gamma - GENIE 2000, we assessed internal exposure based on measurements of I-131 activity in urine and thyroid. In conclusion, we can say that proper organisation of the work in well designet isotopic laboratory and use at indispensable shields can delimit to minimum exposure of medical staff on ionising radiation even in case of work with opened radioactive sources of large activity.